2023
DOI: 10.3390/d15060790
|View full text |Cite
|
Sign up to set email alerts
|

Signals of Pig Ancestry in Wild Boar, Sus scrofa, from Eastern Austria: Current Hybridisation or Incomplete Gene Pool Differentiation and Historical Introgressions?

Denise Böheim,
Felix Knauer,
Milomir Stefanović
et al.

Abstract: In wild boar, Sus scrofa, from Europe, domestic pig-typical ancestry is traced at varying levels. We hypothesised wild boar with pig-typical gene pool characteristics, i.e., “introgression”, congregate more in peri-urban habitats, because of less shyness and better adaptation to anthropogenic stress. We used 16 microsatellites to study introgression levels of 375 wild boar from peri-urban Vienna, Austria, and rural regions in comparison to commercial slaughter pigs, Mangaliza, and Turopolje pigs. We also expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 31 publications
4
9
0
Order By: Relevance
“…While collection date and location were available for most of the samples, no specific information was provided on the phenotypic appearance of individual wild boars, such as suspicious fur coloration, that could have given an indication of introgression by pigs. In addition, we used tissue samples from twenty Mangulica, i.e., Serbian Mangaliza, collected in 2014 at Ravno Selo (Bačka, Vojvodina), and of four Hungarian Mangaliza pigs, purchased from a butcher in eastern Austria (at Pamhagen, Province of Burgenland), as well as 48 commercial slaughter pigs (CSP), purchased as pork packages in 2017 and 2018 from supermarkets in Austria, Germany, the Czech Republic, Hungary, Slovenia, and Bulgaria, all of which have already been used in a study for comparison with Austrian wild boars (Böheim et al, 2023).…”
Section: Wild Boar and Pig Samplesmentioning
confidence: 99%
See 4 more Smart Citations
“…While collection date and location were available for most of the samples, no specific information was provided on the phenotypic appearance of individual wild boars, such as suspicious fur coloration, that could have given an indication of introgression by pigs. In addition, we used tissue samples from twenty Mangulica, i.e., Serbian Mangaliza, collected in 2014 at Ravno Selo (Bačka, Vojvodina), and of four Hungarian Mangaliza pigs, purchased from a butcher in eastern Austria (at Pamhagen, Province of Burgenland), as well as 48 commercial slaughter pigs (CSP), purchased as pork packages in 2017 and 2018 from supermarkets in Austria, Germany, the Czech Republic, Hungary, Slovenia, and Bulgaria, all of which have already been used in a study for comparison with Austrian wild boars (Böheim et al, 2023).…”
Section: Wild Boar and Pig Samplesmentioning
confidence: 99%
“…We used the same sixteen microsatellite markers, i.e., S0002, S0097, S0101, S0155, S0215, SW24, SW72, SW122, SW240, SW461, SW857, SW936, SW1492, SW2021, SW2496, SW2532, as in Böheim et al (2023) to determine allelic variation and individual overall genotypes for population genetic statistics and as a basis for estimating individual introgression of wild boars by pigs. For DNA extraction, purification, and PCR specifications we followed the procedures detailed in Vetter et al (2014;2016) and applied also by Böheim et al (2023). Marker individuals of the latter study were used to synonymize the currently identified alleles and genotypes with those of the latter study, which enabled a direct comparison of the population genetic results.…”
Section: Genetic Markers and Laboratory Proceduresmentioning
confidence: 99%
See 3 more Smart Citations